The Rules of Nakirah and Ma'rifah in Surah Al-Insyirah Verses 5–6: Linguistic Analysis and Interpretation - Ibrahim Arif; Misnawati Misnawati (Lembaga Yasin AlSys, 2026)
Linguistic analysis plays an important role in uncovering the semantic depth and rhetorical beauty of the Qur’an, particularly through the study of definiteness and indefiniteness in Arabic grammar. This study aims to examine the application of the principles of al-nakirah and al-ma’rifah in Surah Al-Inshirah verses 5–6 and analyze their implications for Qur’anic interpretation. This research employed a library-based method using linguistic and exegetical approaches through the analysis of classical and contemporary works on Arabic grammar, rhetoric, and Qur’anic exegesis. The findings reveal that the word al-‘usr (العسر) appears in the definite form (ma’rifah) in both verses, indicating the same specific hardship. In contrast, the word yusran (يسرا) appears in the indefinite form (nakirah), indicating diverse and multiple forms of ease. Based on the grammatical principle governing the repetition of definite and indefinite nouns, the repetition of a definite noun refers to the same entity, whereas the repetition of an indefinite noun implies different or multiple meanings. Therefore, Surah Al-Inshirah verses 5–6 convey the theological and rhetorical message that one hardship will not overcome the many forms of ease granted by Allah. This study concludes that understanding the principles of al-nakirah and al-ma’rifah is essential for achieving a deeper, more accurate, and comprehensive interpretation of Qur’anic meaning. The study contributes to Qur’anic linguistics by demonstrating how Arabic grammatical structures support exegetical precision and enrich the interpretation of Qur’anic rhetoric.